2020
DOI: 10.2147/rmhp.s258812
|View full text |Cite
|
Sign up to set email alerts
|

<p>Perceived Competition and Process of Care in Rural China</p>

Abstract: Purpose: Although there is much debate about the effect of hospital competition on healthcare quality, its impact on the process of care remains unclear. This study aimed to determine whether hospital competition improves the process of care in rural China. Patients and Methods: The county hospital questionnaire survey data and the randomly sampled medical records of bacterial pneumonia patients in 2015 in rural area of Guizhou, China, were used in this study. The processes of care for bacterial pneumonia were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Although, as mentioned above, studies on the process dimension of QoC in China are very few, we still identified 2 possible relevant studies. Lin conducted a study on the quality of pneumonia care of 24 hospitals across southwestern China and utilized 3 QoC indicators: (1) oxygenation assessment, (2) antibiotic treatment, and (3) first antibiotic treatment within 6 h after admission [ 37 ], of which 2 are the same as our study. As estimated by Lin, 2.3% of the included pneumonia patients received blood oxygenation assessment, which in our study was 34.04%, and 91.1% received first antibiotic treatment within 6 h after admission [ 37 ], which in our study was 88.75%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, as mentioned above, studies on the process dimension of QoC in China are very few, we still identified 2 possible relevant studies. Lin conducted a study on the quality of pneumonia care of 24 hospitals across southwestern China and utilized 3 QoC indicators: (1) oxygenation assessment, (2) antibiotic treatment, and (3) first antibiotic treatment within 6 h after admission [ 37 ], of which 2 are the same as our study. As estimated by Lin, 2.3% of the included pneumonia patients received blood oxygenation assessment, which in our study was 34.04%, and 91.1% received first antibiotic treatment within 6 h after admission [ 37 ], which in our study was 88.75%.…”
Section: Discussionmentioning
confidence: 99%
“…Lin conducted a study on the quality of pneumonia care of 24 hospitals across southwestern China and utilized 3 QoC indicators: (1) oxygenation assessment, (2) antibiotic treatment, and (3) first antibiotic treatment within 6 h after admission [ 37 ], of which 2 are the same as our study. As estimated by Lin, 2.3% of the included pneumonia patients received blood oxygenation assessment, which in our study was 34.04%, and 91.1% received first antibiotic treatment within 6 h after admission [ 37 ], which in our study was 88.75%. Although the latter indicator in southwestern China seems a bit better than that in eastern China, the former indicator suggests great differences between the 2 places.…”
Section: Discussionmentioning
confidence: 99%
“…Only 8 respondents (3.7%) reported the absence of perceived competition. Based on previous research, 43 “no competition” and “moderate competition” were defined as low competition groups (as references) with an assigned value of zero, and “intense competition” was defined as the high competition group with an assigned value of one. Directors who reported the perception of intense competition or moderate competition were further asked about where the competition pressure mainly came from, which included multiple potential sources namely hospitals out of the county, public hospitals within the county, private hospitals within the county, or other.…”
Section: Methodsmentioning
confidence: 99%